2020
DOI: 10.1080/02673037.2020.1829564
|View full text |Cite
|
Sign up to set email alerts
|

Understanding responses to homelessness during COVID-19: an examination of Australia

Abstract: Following the outbreak of COVID-19, governments have spent unprecedented sums of money to accommodate people experiencing homelessness, often in underutilized hotels. This intervention contrasts with the policy stasis and "poverty of ambition" that characterized responses to rising homelessness over the past decade in countries such as Australia, the UK, the US, and much of Europe. This is a situation that has prevailed despite rigorous evidence on both the harms of homelessness and the ability of policy to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 35 publications
0
58
0
3
Order By: Relevance
“…The US government announced $4 billion to prevent and respond to homelessness during COVID-19. The New Zealand, Canadian and French Governments each committed the equivalent of hundreds of millions of Australian dollars to temporarily accommodate homeless people during COVID-19 (Parsell, Clarke and Kuskoff 2020). In the UK, the government allocated £105 million, and it was reported that 90% of rough sleepers known to councils were offered accommodation as part of the COVID-19 response (Fitzpatrick et al 2020).…”
Section: Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…The US government announced $4 billion to prevent and respond to homelessness during COVID-19. The New Zealand, Canadian and French Governments each committed the equivalent of hundreds of millions of Australian dollars to temporarily accommodate homeless people during COVID-19 (Parsell, Clarke and Kuskoff 2020). In the UK, the government allocated £105 million, and it was reported that 90% of rough sleepers known to councils were offered accommodation as part of the COVID-19 response (Fitzpatrick et al 2020).…”
Section: Housingmentioning
confidence: 99%
“…Over and above the forecast spend on homelessness for general services, during COVID-19 Australia's five mainland states have spent an approximate $229 million to respond to people who are homeless during COVID-19. The lion's share of this has been to pay for temporary accommodation to support people sleeping rough to move off the streets (Parsell, Clarke and Kuskoff 2020). The temporary accommodation has primarily been hotel accommodation, which was vacant because of the COVID-19 travel restrictions.…”
Section: Housingmentioning
confidence: 99%
“…This article derives from a policy project focused on the impact of COVID-19 on housing in the Region of Waterloo (Doucet & Van der Merwe, 2020). We employ a critical content review of media, research, and policy reports, particularly during the first wave of the pandemic (March-August 2020) (for other examples of this approach, see: Parsell et al, 2020;Rogers & Powers, 2020;Vilenica et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, as other researchers have also noted, many such measures enacted quickly during the pandemic have been designed to be temporary. Parsell et al (2020) examined responses to homelessness in Australia and found that many measures were implemented, not out of concern for the health and well-being of homeless populations, but from the perspective of wider public health, where unsheltered populations are seen as a threat to the wider population. In Waterloo Region, using hotels as shelters, ABTC, bans on evictions, and the lack of bylaw enforcement against homeless encampments are all temporary and little, if anything, has been done to address either the chronic lack of affordable housing in the region, or the commodification of housing and exploitation by landlords.…”
Section: Affordable Housing: Growing Demand Across the Spectrummentioning
confidence: 99%
“…Governments around the world have responded to COVID‐19 differently. Since the pandemic was declared by the World Health Organization in March 2020, 2 we have witnessed significant social policy reforms in Australia with the rapid introduction of evidence‐based (and at times, long‐debated) policy change, including free childcare, 3 accommodation for people experiencing homelessness, 4 wage subsidies, 5 widespread uptake of flexible and remote working arrangements, 6 and the rollout of telehealth 7 . Despite the temporary nature of some reforms, it is indisputable that change is in the air.…”
mentioning
confidence: 99%